Legal Implications of Consumer Protection on Healthcare Access: A Qualitative Study of Consumer Experience in Community Health Centers - Yuyut Prayuti; Arman Lany; Budi Santosa; Sella Romika Juliantary; Risqi Antoni (ARRUS Journal of Social Sciences and Humanities, 2024)
This study aims to explore the application of consumer protection law to health access services from the perspective of society. The research method used is qualitative with a descriptive approach. Primary data were obtained through interviews and observations, while secondary data were obtained from relevant literature reviews. The results showed that healthcare users in community health centers experienced variations in satisfaction, selection factors, quality of service, problems faced, and consumer protection. The main factors influencing the selection of a health center are location, quality of service, and reputation. Although most respondents were satisfied with the friendly and efficient service, they also complained of a lack of information and slow administrative processes. Variations in assessments of service quality include medical staff competence, waiting times, and levels of coordination. Problems include excessively long waiting times, lack of clear information, and lack of communication between medical staff and administration. Consumer protection is also a concern, especially related to access to patient rights information and the fulfillment of these rights.